1987
DOI: 10.1161/01.hyp.10.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Renal phospholipase C and diglyceride lipase activity in spontaneously hypertensive rats.

Abstract: SUMMARY Phospholipase C activity and diglyceride lipase activity were studied in the renal cortex and medulla of 10-and 40-week-old stroke-prone spontaneously hypertensive rats (SHRSP) and agematched normotensive Wistar-Kyoto rats (WKY). Enhanced phospholipase C activity was found in the cortical and medullary cytosol of kidney from SHRSP, and microsomal diglyceride lipase in SHRSP also increased. In SHRSP, phospholipase C and diglyceride lipase activities increased with age, but this increase was not evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…PLA, activity, by contrast, was not elevated in SHRs and was not correlated with BP. Similar increases in basal PLC have been reported in nonvascular tissues of SHRs including red blood cells (45), platelets (82), and kidney (46).…”
Section: Spontaneously Hypertensive Ratsupporting
confidence: 80%
“…PLA, activity, by contrast, was not elevated in SHRs and was not correlated with BP. Similar increases in basal PLC have been reported in nonvascular tissues of SHRs including red blood cells (45), platelets (82), and kidney (46).…”
Section: Spontaneously Hypertensive Ratsupporting
confidence: 80%
“…However, consistent with our findings, there is a report of increased phospholipase C activity in SHR compared with WKY rats. 23 The result of this study cannot identify the specific sites of renal DA-1 receptor phospholipase C signal transduction pathway that are affected in the adult SHR. However, it is possible that the sites involved are distal to the dopamine receptors, since there are reports that showed no differences in renal tubular DA-1 receptor number, distribution, or affinity between WKY rats and SHR of this age, 10 -17 although in 32-week-old SHR, the renal tubular DA-1 receptors were reported to be decreased.…”
Section: Discussionmentioning
confidence: 85%
“…This could occur if the local production of these metabo lites were elevated in the renal vasculature of SHR or the degradation rate of cytochrome P-450 arachidonic acid metabolites in renal cortical tissue were reduced. In addi tion, Kawaguchi et al [24] have reported that phospholi pase A and C activity is enhanced in the kidney of adult SHR. Enhanced phospholipase activity could alter the production of cytochrome P-450 metabolites of arachi donic acid by elevating substrate availability independent of any differences in cytochrome P-450 activity.…”
Section: Discussionmentioning
confidence: 95%